Low-cost super-corrosion-resistant high-strength wrought magnesium alloy and preparation method thereof
By adding suitable alloying elements to the magnesium alloy and adopting a simple process to regulate its microstructure, the problems of low strength and poor corrosion resistance of magnesium alloy at room temperature are solved, and ultra-corrosion and high-strength magnesium are achieved Alloys suitable for multiple high-performance applications.
Patent Information
- Application Number
- CN202411476325.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
AI Technical Summary
Magnesium alloys have low strength and poor corrosion resistance at room temperature, which hinder their large-scale application.
The Mg-Al-Zn-Mn-Ca alloy is used to regulate the microstructure of the alloy through alloy smelting, solid solution aging treatment and extrusion hot deformation, and improve its corrosion resistance and mechanical properties.
It realizes ultra-corrosion resistance and high strength of magnesium alloys, reduces production costs, is suitable for large-scale production, and meets the performance requirements of 5G communications, aerospace and other fields.
Smart Images

Figure CN119433313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnesium alloy and a preparation method thereof. Background Art
[0002] Due to its advantages such as low density, high specific strength and good recyclability, magnesium alloys have received close attention in many aspects such as lightweight, energy saving and environmental protection. At present, magnesium alloys have been widely used in 5G communications, 3C products, new energy vehicles, aerospace and other fields, and are considered to be an excellent lightweight and high-strength engineering structural material that can replace steel and aluminum alloys. However, the low strength and poor corrosion resistance of magnesium alloys at room temperature are the main reasons hindering their large-scale application.
[0003] In the current technical field, researchers usually introduce a second phase into magnesium alloys by alloying to improve the mechanical properties of magnesium alloys. However, the corrosion potential of most second phases is higher than that of the magnesium matrix, causing the magnesium matrix, which acts as an anode during the corrosion process, to suffer severe microgalvanic corrosion. In addition, the corrosion products of magnesium are mainly Mg(OH)2 and MgO, which are loose and porous and have little resistance to corrosive media. In order to solve the problems of poor corrosion resistance and low strength, most researchers choose to add rare earth elements or adopt more complex and severe plastic deformation processes. Although this can significantly improve the corrosion resistance, it also leads to a significant increase in cost, which is a huge challenge for the large-scale application of magnesium alloys.
[0004] Therefore, it is particularly urgent and has great application value to select suitable non-rare earth alloying elements and simple preparation technology, regulate its microstructure, improve the corrosion resistance and mechanical properties of magnesium alloys synergistically, and realize the integration of magnesium alloy structure and function. Summary of the invention
[0005] In order to solve the problems of poor corrosion resistance and low strength of existing magnesium alloys, the present invention provides a low-cost ultra-corrosion-resistant and high-strength deformable magnesium alloy and a preparation method thereof.
[0006] The low-cost super corrosion-resistant high-strength deformable magnesium alloy of the present invention is a Mg-Al-Zn-Mn-Ca alloy, wherein the content of Al is 5-9wt.%, the content of Zn is 0.6-2%, the content of Mn is 0.1-0.5%, the content of Ca is 0-2%, and the balance is Mg and inevitable impurities.
[0007] The method for preparing the low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy of the present invention is carried out according to the following steps:
[0008] 1. Weigh the raw materials according to the mass ratio of the elements in the Mg-Al-Zn-Mn-Ca alloy and pretreat the raw materials;
[0009] 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, and obtaining an alloy ingot after cooling;
[0010] The smelting process is as follows: firstly, a pure Mg ingot is melted, then a Mg-Ca master alloy, a Mg-Zn master alloy and a Mg-Mn master alloy are added until they are completely melted and kept warm for 20-25 minutes, then a Mg-Al master alloy is added, and after being completely melted, the master alloy is stirred, and the master alloy is kept warm to obtain a magnesium alloy melt and remove surface scum, and finally, the magnesium alloy melt is water-cooled in a protective atmosphere to form an ingot, and the smelting is completed;
[0011] 3. The alloy ingot obtained in step 2 is prepared into a cylindrical billet for extrusion, the cylindrical billet for extrusion is subjected to a solid solution treatment, and then subjected to an aging treatment and water cooling to obtain a heat-treated cylindrical billet for extrusion, and the heat-treated cylindrical billet for extrusion is subjected to extrusion deformation and water cooling, and the process is completed;
[0012] The solution treatment is a primary solution treatment, the solution treatment temperature is 400-520°C, and the time is 2-24h; or the solution treatment is a secondary solution treatment, firstly keeping the temperature at 400°C-420°C for 12-48h, and then keeping the temperature at 450°C-500°C for 3-10h;
[0013] The aging treatment temperature is 200-350°C and the time is 2-48h;
[0014] The extrusion ratio of the extrusion deformation is (10-30):1, and the extrusion rate is 0.1-5 mm / s.
[0015] The principles and beneficial technical effects of the present invention are as follows:
[0016] 1. The present invention obtains a super corrosion-resistant and high-strength magnesium alloy with excellent comprehensive performance by adding appropriate alloying elements, using simple alloy smelting, solid solution aging treatment and extrusion hot deformation. The prepared super corrosion-resistant and high-strength magnesium alloy solves the problem of mismatch between corrosion resistance and strength of magnesium alloy through fine dispersed precipitation phase and grain refinement. In addition, the preparation method provided by the present invention has simple equipment requirements, short process flow, convenient operation, high preparation efficiency, low cost, and is suitable for large-scale production.
[0017] 2. The magnesium alloy prepared by the present invention is immersed in a 3.5wt.% NaCl aqueous solution at room temperature for 14 days. The corrosion rate obtained by the hydrogen evolution experiment is 0.086-0.374mm / y. At the same time, the yield strength of the magnesium alloy is 205.64-272.19MPa, the tensile strength is 307.03-375.08MPa, and the elongation is 5.91%-16.35%. The magnesium alloy prepared by the present invention has excellent comprehensive performance and can effectively meet the performance requirements of components such as 5G communications, radars, and 3C products. It has broad application prospects in the fields of aerospace, automobiles, and electronics.
[0018] 3. In the present invention, by selecting the appropriate content of alloying elements Al, Zn, Mn, and Ca, and adopting casting, heat treatment, extrusion and other processes to control the microstructure of the alloy, the solid solution treatment allows most of the network second phase to dissolve back into the matrix, and then through aging treatment, the second phase is precipitated in the form of fine dispersed continuous or semi-continuous needles. During the thermal deformation process, the fine dispersed second phase prevents dislocation movement, thereby refining the magnesium alloy grains and forming a micron-level equiaxed grain distribution, thereby improving the mechanical properties of the alloy. Extrusion deformation causes a large number of needle-shaped Mg-Al phases and Mg-Al-Ca phases in the alloy to be broken into fine particles and dispersed and evenly distributed. Therefore, the alloy prepared by the present invention has super corrosion resistance while maintaining high strength. In addition, Mn can react with the impurity Fe in the material, thereby reducing the content of impurity Fe. At the same time, the dense corrosion products Al2O3, Al(OH)3, and Ca(OH)2 formed by the alloy elements Al and Ca during the corrosion process can enhance the density and stability of the loose and porous MgO2 and Mg(OH)2 corrosion product films, thereby improving their protective effect on the alloy matrix. Therefore, the alloy also has excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The metallographic structure of the as-cast Mg-Al-Zn-Mn alloy prepared in step 2 of Example 1;
[0020] Figure 2 The metallographic structure of the solid solution Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1;
[0021] Figure 3 The metallographic structure of the aged Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1;
[0022] Figure 4 The metallographic structure of the extruded Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1;
[0023] Figure 5 The scanning electron microscope structure of the extruded Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1;
[0024] Figure 6 The tensile engineering stress-engineering strain curve of the extruded Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1;
[0025] Figure 7 The hydrogen evolution amount-time curve of the extruded Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1;
[0026] Figure 8 The SEM cross-sectional morphology and element surface distribution diagram of the corrosion product film of the extruded Mg-Al-Zn-Mn alloy prepared in step 3 of Example 1 after being immersed in a 3.5wt% NaCl solution for 3 days. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0028] Specific implementation method 1: In this implementation method, the low-cost super corrosion-resistant and high-strength deformable magnesium alloy is a Mg-Al-Zn-Mn-Ca alloy, wherein the Al content is 5-9wt.%, the Zn content is 0.6-2%, the Mn content is 0.1-0.5%, the Ca content is 0-2%, and the balance is Mg and unavoidable impurities.
[0029] This embodiment has the following beneficial effects:
[0030] 1. This embodiment adds appropriate alloying elements, and uses simple alloy smelting, solution aging treatment and extrusion hot deformation to obtain a super corrosion-resistant and high-strength magnesium alloy with excellent comprehensive performance. The prepared super corrosion-resistant and high-strength magnesium alloy solves the problem of mismatch between corrosion resistance and strength of magnesium alloys through fine dispersed precipitation phases and grain refinement. In addition, the preparation method provided in this embodiment has simple equipment requirements, short process flow, convenient operation, high preparation efficiency, low cost, and is suitable for large-scale production.
[0031] 2. The magnesium alloy prepared in this embodiment is immersed in a 3.5wt.% NaCl aqueous solution at room temperature for 14 days. The corrosion rate obtained by the hydrogen evolution experiment is 0.086-0.374mm / y. At the same time, the yield strength of the magnesium alloy is 205.64-272.19MPa, the tensile strength is 307.03-375.08MPa, and the elongation is 5.91%-16.35%. The magnesium alloy prepared in this embodiment has excellent comprehensive performance and can effectively meet the performance requirements of components such as 5G communications, radars, and 3C products. It has broad application prospects in the fields of aerospace, automobiles, and electronics.
[0032] 3. In this embodiment, by selecting the appropriate content of alloying elements Al, Zn, Mn, and Ca, and using casting, heat treatment, extrusion and other processes to control the microstructure of the alloy, the solid solution treatment allows most of the network second phase to dissolve back into the matrix, and then through aging treatment, the second phase is precipitated in the form of fine and dispersed continuous or semi-continuous needles. During the thermal deformation process, the fine and dispersed second phase prevents dislocation movement, thereby refining the magnesium alloy grains and forming a micron-level equiaxed grain distribution, thereby improving the mechanical properties of the alloy. Extrusion deformation causes a large number of needle-shaped Mg-Al phases and Mg-Al-Ca phases in the alloy to break into fine particles and disperse them evenly. Therefore, the alloy prepared in this embodiment has super corrosion resistance while maintaining high strength. In addition, Mn can react with the impurity Fe in the material, thereby reducing the content of impurity Fe. At the same time, the dense corrosion products Al2O3, Al(OH)3, and Ca(OH)2 formed by the alloy elements Al and Ca during the corrosion process can enhance the density and stability of the loose and porous MgO2 and Mg(OH)2 corrosion product films, thereby improving their protective effect on the alloy matrix. Therefore, the alloy also has excellent corrosion resistance.
[0033] Specific implementation method 2: The preparation method of low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy in this implementation method is carried out according to the following steps:
[0034] 1. Weigh the raw materials according to the mass ratio of the elements in the Mg-Al-Zn-Mn-Ca alloy and pretreat the raw materials;
[0035] 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, and obtaining an alloy ingot after cooling;
[0036] The smelting process is as follows: firstly, a pure Mg ingot is melted, then a Mg-Ca master alloy, a Mg-Zn master alloy and a Mg-Mn master alloy are added until they are completely melted and kept warm for 20-25 minutes, then a Mg-Al master alloy is added, and after being completely melted, the master alloy is stirred, and the master alloy is kept warm to obtain a magnesium alloy melt and remove surface scum, and finally, the magnesium alloy melt is water-cooled in a protective atmosphere to form an ingot, and the smelting is completed;
[0037] 3. The alloy ingot obtained in step 2 is prepared into a cylindrical billet for extrusion, the cylindrical billet for extrusion is subjected to a solid solution treatment, and then subjected to an aging treatment and water cooling to obtain a heat-treated cylindrical billet for extrusion, and the heat-treated cylindrical billet for extrusion is subjected to extrusion deformation and water cooling, and the process is completed;
[0038] The solution treatment is a primary solution treatment, the solution treatment temperature is 400-520°C, and the time is 2-24h; or the solution treatment is a secondary solution treatment, firstly keeping the temperature at 400°C-420°C for 12-48h, and then keeping the temperature at 450°C-500°C for 3-10h;
[0039] The aging treatment temperature is 200-350°C and the time is 2-48h;
[0040] The extrusion ratio of the extrusion deformation is (10-30):1, and the extrusion rate is 0.1-5 mm / s.
[0041] 1. This embodiment adds appropriate alloying elements, and uses simple alloy smelting, solution aging treatment and extrusion hot deformation to obtain a super corrosion-resistant and high-strength magnesium alloy with excellent comprehensive performance. The prepared super corrosion-resistant and high-strength magnesium alloy solves the problem of mismatch between corrosion resistance and strength of magnesium alloys through fine dispersed precipitation phases and grain refinement. In addition, the preparation method provided in this embodiment has simple equipment requirements, short process flow, convenient operation, high preparation efficiency, low cost, and is suitable for large-scale production.
[0042] 2. The magnesium alloy prepared in this embodiment is immersed in a 3.5wt.% NaCl aqueous solution at room temperature for 14 days. The corrosion rate obtained by the hydrogen evolution experiment is 0.086-0.374mm / y. At the same time, the yield strength of the magnesium alloy is 205.64-272.19MPa, the tensile strength is 307.03-375.08MPa, and the elongation is 5.91%-16.35%. The magnesium alloy prepared in this embodiment has excellent comprehensive performance and can effectively meet the performance requirements of components such as 5G communications, radars, and 3C products. It has broad application prospects in the fields of aerospace, automobiles, and electronics.
[0043] 3. In this embodiment, by selecting the appropriate content of alloying elements Al, Zn, Mn, and Ca, and using casting, heat treatment, extrusion and other processes to control the microstructure of the alloy, the solid solution treatment allows most of the network second phase to dissolve back into the matrix, and then through aging treatment, the second phase is precipitated in the form of fine and dispersed continuous or semi-continuous needles. During the thermal deformation process, the fine and dispersed second phase prevents dislocation movement, thereby refining the magnesium alloy grains and forming a micron-level equiaxed grain distribution, thereby improving the mechanical properties of the alloy. Extrusion deformation causes a large number of needle-shaped Mg-Al phases and Mg-Al-Ca phases in the alloy to break into fine particles and disperse them evenly. Therefore, the alloy prepared in this embodiment has super corrosion resistance while maintaining high strength. In addition, Mn can react with the impurity Fe in the material, thereby reducing the content of impurity Fe. At the same time, the dense corrosion products Al2O3, Al(OH)3, and Ca(OH)2 formed by the alloy elements Al and Ca during the corrosion process can enhance the density and stability of the loose and porous MgO2 and Mg(OH)2 corrosion product films, thereby improving their protective effect on the alloy matrix. Therefore, the alloy also has excellent corrosion resistance.
[0044] Specific implementation method three: This implementation method is similar to specific implementation method two in that: the raw material in step one is pure Mg ingot, Mg-Zn master alloy, Mg-Al master alloy, Mg-Mn master alloy and Mg-Ca master alloy.
[0045] Specific implementation method 4: This implementation method is different from specific implementation method 2 in that: the process of pre-treating the raw material in step 1 is: grinding the raw material with sandpaper to remove surface oxide scale and impurities.
[0046] Specific embodiment 5: This embodiment is similar to specific embodiment 2 in that the temperature of the preheating treatment in step 2 is 250-350°C.
[0047] Specific implementation method six: This implementation method is different from specific implementation method two in that the gas of the protective atmosphere in step two is a mixed gas of SF6 and CO2, and the proportion of SF6 in the mixed gas is 2% to 3%.
[0048] Specific implementation method seven: This implementation method is similar to specific implementation method two in that the stirring time after complete melting in step two is 3 to 5 minutes.
[0049] Specific implementation eight: This implementation is similar to specific implementation two in that: the standing and heat preservation time in step two is 10 to 20 minutes.
[0050] Specific embodiment 9: This embodiment is similar to specific embodiment 2 in that: the melting temperature of the pure Mg ingot in step 2 is 700-760°C.
[0051] Specific embodiment ten: This embodiment is different from specific embodiment two in that: before the extrusion deformation in step three, the step of preheating the cylindrical billet for extrusion and the extrusion die is also included; the preheating temperature is 300-450°C and the time is 10-30 minutes.
[0052] Embodiment 1:
[0053] The method for preparing the low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy of this embodiment is carried out according to the following steps:
[0054] 1. Weigh the raw materials according to the mass ratio of the elements in the Mg-Al-Zn-Mn alloy and pretreat the raw materials;
[0055] The super corrosion-resistant and high-strength alloy is a Mg-Al-Zn-Mn alloy, wherein the content of Al is 7.8wt.%, the content of Zn is 0.72wt.%, the content of Mn is 0.21wt.%, and the balance is Mg and unavoidable impurities.
[0056] The raw materials are pure Mg ingot, Mg-30wt.%Al master alloy, Mg-30wt.%Zn master alloy and Mg-3wt.%Mn master alloy;
[0057] The process of pre-treating the raw material is: grinding the raw material with sandpaper to remove the surface oxide scale and impurities;
[0058] 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, and obtaining an alloy ingot after cooling;
[0059] The temperature of the preheating treatment is 300°C;
[0060] The protective atmosphere gas is a mixture of SF6 and CO2, and the proportion of SF6 in the mixture is 2.4%;
[0061] The smelting process is as follows: firstly, a pure Mg ingot is melted, then a Mg-30wt.% Zn master alloy and a Mg-3wt.% Mn master alloy are added, the alloy is completely melted, and then the alloy is kept warm for 25 minutes, then a Mg-30wt.% Al master alloy is added, and after the alloy is completely melted, the alloy is stirred, and then the alloy is kept warm to obtain a magnesium alloy melt, and surface scum is removed; finally, the magnesium alloy melt is water-cooled in a protective atmosphere to form an ingot, and the smelting is completed;
[0062] The melting temperature of the pure Mg ingot is 760°C;
[0063] The stirring time after complete melting is 4 minutes;
[0064] The standing and heat preservation time is 15min;
[0065] 3. The alloy ingot obtained in step 2 is prepared into a cylindrical billet for extrusion with a height of 26 mm and a diameter of 47 mm, the cylindrical billet for extrusion is subjected to solid solution treatment, and then subjected to aging treatment and water cooling to obtain a heat-treated cylindrical billet for extrusion, the heat-treated cylindrical billet for extrusion is subjected to extrusion deformation and water cooling treatment, and the extruded Mg-7.8Al-0.72Zn-0.21Mn is obtained;
[0066] The solution treatment temperature is 420°C and the time is 24h;
[0067] The aging treatment temperature is 300°C and the time is 12h;
[0068] The extrusion deformation also includes a preheating step of the cylindrical billet and the extrusion die; the preheating temperature is 350°C and the time is 20 minutes;
[0069] The extrusion ratio of the extrusion deformation is 30:1, and the extrusion rate is 0.1 mm / s.
[0070] At 25°C, the corrosion rate of the extruded Mg-7.8Al-0.72Zn-0.21Mn prepared in this embodiment was 0.086 mm / y in a hydrogen evolution experiment after being immersed in a 3.5 wt.% NaCl solution for 14 days. The corrosion resistance is far superior to that of pure Mg. The yield strength is 272.19 MPa, the tensile strength is 375.08 MPa, and the elongation is 16.35%. The comprehensive performance exceeds that of most magnesium alloys.
[0071] Figure 1 The microstructure of the cast Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 2 of Example 1 is mainly composed of an α-Mg matrix and a eutectic structure along the grain boundaries, and the eutectic structure is approximately in the form of a continuous network. Figure 2 This is the microstructure of the solid solution Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1. The second phase is basically dissolved back into the matrix, and only a small amount of Al-Mn phase exists. Figure 3 This is the microstructure of the aged Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1. The second phase appears uniformly dispersed in the form of fine needles. Figure 4 The metallographic structure of the extruded Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1; Figure 4 It can be seen that the precipitated phase in the alloy after extrusion is broken into fine particles and evenly dispersed, which can play the role of second phase strengthening and pinning the grain boundaries, greatly refining the recrystallized grains and improving the corrosion resistance and strength of the alloy. Figure 5 This is the scanning electron microscope structure of the extruded Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1. Figure 6 This is the tensile engineering stress-engineering strain curve of the extruded Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1. Figure 7 The hydrogen evolution amount-time curve of the extruded Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1; Figure 7 It can be seen that with the increase of time, the amount of hydrogen evolution gradually increases, but the increase is very small. The average corrosion rate for 14 days is calculated to be 0.086mm / y. Figure 8 The SEM cross-sectional morphology and element surface distribution diagram of the corrosion product film of the extruded Mg-7.8Al-0.72Zn-0.21Mn alloy prepared in step 3 of Example 1 after being immersed in 3.5wt% NaCl solution for 3 days show that the degree of corrosion is small and the Al content in the corrosion product is consistent with that in the matrix, indicating that the organization has strong resistance to corrosive media.
[0072] Embodiment 2:
[0073] The difference between this embodiment and embodiment 1 is that in the step of preheating the cylindrical billet and the extrusion die before extrusion deformation in step 3, the preheating temperature is 400° C. and the time is 20 minutes. The rest is the same as embodiment 1.
[0074] The corrosion rate of the extruded Mg-Al-Zn-Mn prepared in this embodiment immersed in a 3.5wt.% NaCl solution for 14 days in a hydrogen evolution experiment was 0.286mm / y, the alloy yield strength was 205.64MPa, the tensile strength was 343.81MPa, and the elongation was 16.02%.
[0075] Embodiment 3:
[0076] The difference between this embodiment and embodiment 2 is that the magnesium alloy described in step 1 is a Mg-Al-Zn-Mn-Ca alloy, wherein the content of Al is 7.74wt.%, the content of Zn is 0.77wt.%, the content of Mn is 0.14wt.%, the content of Ca is 0.32wt.%, and the balance is Mg. The solid solution treatment before extrusion deformation described in step 3 is a secondary solid solution treatment, firstly keeping warm at 420℃ for 24h, and then keeping warm at 450℃ for 3h; in the preheating step of the extrusion cylindrical billet and the extrusion die before extrusion deformation described in step 3, the preheating temperature is 400℃ and the time is 20min. The rest is the same as embodiment 2.
[0077] The corrosion rate of the extruded Mg-Al-Zn-Mn-Ca prepared in this embodiment, which was immersed in a 3.5wt.% NaCl solution for 14 days, was 0.137mm / y, the alloy yield strength was 211.48MPa, the tensile strength was 307.03MPa, and the elongation was 5.91%.
[0078] Embodiment 4:
[0079] The difference between this embodiment and embodiment 3 is that in the preheating step of the extrusion cylindrical billet and the extrusion die before extrusion deformation in step 3, the preheating temperature is 450°C and the time is 20 minutes. The rest is the same as embodiment 3. The corrosion rate of the extruded Mg-Al-Zn-Mn-Ca prepared in this embodiment obtained by soaking in 3.5wt.% NaCl solution for 14 days and the hydrogen evolution experiment is 0.373mm / y, the alloy yield strength is 223.82MPa, the tensile strength is 329.88MPa, and the elongation is 9.95%.
Claims
1. A low-cost, ultra-corrosion-resistant, high-strength deformable magnesium alloy, characterized in that: The low-cost super corrosion-resistant and high-strength deformable magnesium alloy is a Mg-Al-Zn-Mn-Ca alloy, in which the Al content is 5-9wt.%, the Zn content is 0.6-2%, the Mn content is 0.1-0.5%, the Ca content is 0-2%, and the balance is Mg and unavoidable impurities.
2. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 1, characterized in that: The preparation method of low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy is carried out according to the following steps:
1. Weigh the raw materials according to the mass ratio of the elements in the Mg-Al-Zn-Mn-Ca alloy and pretreat the raw materials; 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, and obtaining an alloy ingot after cooling; The smelting process is as follows: firstly, a pure Mg ingot is melted, then a Mg-Ca master alloy, a Mg-Zn master alloy and a Mg-Mn master alloy are added until they are completely melted and kept warm for 20-25 minutes, then a Mg-Al master alloy is added, and after being completely melted, the master alloy is stirred, and the master alloy is kept warm to obtain a magnesium alloy melt and remove surface scum, and finally, the magnesium alloy melt is water-cooled in a protective atmosphere to form an ingot, and the smelting is completed; 3. The alloy ingot obtained in step 2 is prepared into a cylindrical billet for extrusion, the cylindrical billet for extrusion is subjected to a solid solution treatment, and then subjected to an aging treatment and water cooling to obtain a heat-treated cylindrical billet for extrusion, and the heat-treated cylindrical billet for extrusion is subjected to extrusion deformation and water cooling, and the process is completed; The solution treatment is a primary solution treatment, the solution treatment temperature is 400-520°C, and the time is 2-24h; or the solution treatment is a secondary solution treatment, firstly keeping the temperature at 400°C-420°C for 12-48h, and then keeping the temperature at 450°C-500°C for 3-10h; The aging treatment temperature is 200-350°C and the time is 2-48h; The extrusion ratio of the extrusion deformation is (10-30):1, and the extrusion rate is 0.1-5 mm / s.
3. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The raw materials in step 1 are pure Mg ingots, Mg-Zn master alloys, Mg-Al master alloys, Mg-Mn master alloys and Mg-Ca master alloys.
4. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The process for pre-treating the raw materials in step 1 is: grinding the raw materials with sandpaper to remove surface oxide scale and impurities.
5. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The temperature of the preheating treatment in step 2 is 250-350°C.
6. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The protective atmosphere gas in step 2 is a mixed gas of SF6 and CO2, and the proportion of SF6 in the mixed gas is 2% to 3%.
7. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The stirring time after complete melting in step 2 is 3 to 5 minutes.
8. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The time of standing and keeping warm in step 2 is 10 to 20 minutes.
9. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: The melting temperature of the pure Mg ingot in step 2 is 700-760°C.
10. The method for preparing a low-cost ultra-corrosion-resistant high-strength deformable magnesium alloy according to claim 2, characterized in that: Step 3: Before the extrusion deformation, the cylindrical billet and the extrusion die are also preheated; the preheating temperature is 300-450°C and the time is 10-30 minutes.
Citation Information
Cited By
High-strength corrosion-resistant magnesium alloy plate and preparation method thereof
CN122358015A